Alloreactivity of Virus-Specific T Cells: Possible Implication of Graft-Versus-Host Disease and Graft-Versus-Leukemia Effects - Fuji, Shigeo; Kapp, Markus; Einsele, Hermann (Frontiers in Immunology, 2013)
Immune reconstitution of functional virus-specific T cells after allogeneic hematopoietic stem cell transplantation (HSCT) has been intensively investigated. However, the possible role of crossreactivity of these virus-specific T cells against allogeneic targets is still unclear. Theoretically, as in the field of organ transplantation, virus-specific T cells possess crossreactivity potential after allogeneic HSCT. Such crossreactivity is assumed to play a role in graft-versus-host disease and graft-versus-leukemia effects. In this article, we aim to give a comprehensive overview of current understanding about crossreactivity of virus-specific T cells.